Judicial review and the law of the constitution - Snowiss, Sylvia (Delhi, 1996)
In this book, the author presents a new interpretation of the origin of judicial review. She traces the development of judicial review from American independence through the tenure of John Marshall as Chief Justice, showing that Marshall's role was far more innovative and decisive than has yet been recognized. According to the author all support for judicial review before Marshall contemplated a fundamentally different practice from that which we know today.
Keywords: Judicial review -United States